Age-Related Changes in Female Murine Reproductive Mucosa with respect to γδ T Cell Presence - Katarzyna Skulska; Anna Ewa Kędzierska; Małgorzata Krzyżowska; Grzegorz Chodaczek (Journal of Immunology Research)
Many studies have demonstrated a general decline and dysregulation in immune functions with age. It is not clear, however, how the aging affects the immune surveillance of the female reproductive tract (FRT) by γδ T cells, a unique population of T lymphocytes that was shown to regulate homeostasis of epithelial barriers. First, we analyzed γδ T cell presence in FRT in young (2 months) and old (18 months) wild-type (WT) C57BL/6 mice. We did not detect any changes in γδ T cell number nor distribution in the vaginas between the age groups, while in uteri, there was a twofold increase in γδ T cell number in aged mice. To check if γδ T lymphocytes regulate a metabolic and immune status of aging vaginal tissue, we compared the expression of 84 aging-associated genes in young and old WT and γδ T-cell-deficient (Tcrd-/-) mice. We discovered that only the Ltf (lactotransferrin) gene was downregulated in old Tcrd-/- mice. In both mouse strains, we found similar age-dependent changes in cytokine production upon vaginal inflammation due to Toll-like receptor 9 (TLR9) stimulation with CpG. With age in the vaginas, IL-1α and IL-17A levels increased while IL-6, IL-10, MCP-1, and IFNγ levels were diminished in response to CpG. Similar trends were observed in uteri. Interestingly, under the inflammatory state, the lack of γδ T cells in young individuals enhanced MCP-1 production in the vagina and decreased MCP-1 level in the uterus in old females. Our gene expression data point to an antimicrobial role of γδ T lymphocytes. The profile of secreted inflammatory cytokines shifted during aging toward the proinflammatory type, and γδ T cells played a modest fine-tuning role in immunoregulation in aged FRT. We believe this work expands our understanding of γδ T cell functions and the inflammaging in the murine reproductive epithelia.